Experimental investigation and fuzzy logic modelling of CO2 laser cutting parameter for AA6061-T6 sheet. (9th January 2020) - Parthiban, A.; Sathish, S.; Ravikumar, R.; Prakash, P.
The laser machining is a thermal energy-based process. The aluminium alloy is a highly reflective material which is difficult to cut by using the laser cutting process. The present paper experimentally investigated about the CO2 laser cutting of aluminium AA6061-T6 alloy material for the improvement of geometrical accuracy of the curved profile at the same time to minimise the top, bottom kerf width and kerf deviations. The experiments are carried out by using fuzzy logic approach and to predict the effect of CO2 laser cutting quality based on the cutting parameters on laser power, cutting speed, gas pressure and focal position. The fuzzy logic model is used on fuzzy logic tool box of MATLAB using Mamdani technique. The relationship between experimental value and fuzzy model are compared. Finally, based on the results, the proposed fuzzy logic models are minimised to top, bottom kerf width and kerf deviations of CO2 laser cutting of AA6061-T6 aluminium alloys.